ADMINISTRATION AND MONITORING OF COMPUTER NETWORKS AS A METHOD OF SOLVING MODERN PROBLEMS IN FINANCIAL SYSTEMS - Tarasenko , Oleksandr; Khristoev , Vladislav; Danilo, Aksynin (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2021)
The article defines the role of administration and monitoring of computer networks in financial systems. The main objectives of monitoring are network activities. Research analysis and task setting are to monitor traffic as an important source of information for effective network management, bringing the main functions of network administrators in financial systems. The effectiveness of monitoring using network traffic analyzers depends on the topology of the network under study, its configuration, and the set of devices from which the network is built. The result of the study in the form of two main needs is monitoring and analysis. Effective network management in the field of finance and banking systems, as well as continuous improvement of software in financial systems. What are the requirements for software agent technology? The main functions and tasks of network administration - a description of monitoring, its tools and network analysis, which are divided into certain classes: protocol analyzers (Protocolanalyzers), system management tools (System Management), network management systems (Network Management Systems), built diagnostic and management systems (Embedded Systems), multifunctional devices for analysis and diagnostics, equipment for diagnostics and certification of cable systems, expert systems. The main functions of monitoring and analysis of network activity in financial systems are in the form of 4 items: performance analysis, network accounting, security management, error handling. The main aspects for the development of software for monitoring network activity, the needs that arise during the work with the network, the peculiarities of the administration of these networks, analyzed the existing software for monitoring network activity in financial systems. An example of the use of software for the administration and monitoring of computer networks is a description of the capabilities and highlighting the advantages and disadvantages of these programs in financial systems. This article discusses the following software: Total Network Monitor 2, Observium, Network Olympus, Zabbix.